Investigation of the Fatigue Crack Propagation Behaviour in the Al Alloy/Hybrid MMC Bi-layer Material - Iqbal, AKM Asif; Arai, Yoshio (IOP Publishing, 2017)
In this study, the fatigue crack propagation behaviour in the Al alloy-hybrid MMC bi-material system has been investigated. Three-point bending fatigue test is carried out on the Shimadzu servopulser machine. The plastic replica technique is used to observe the crack growth during cyclic loading. The crack growth rate is analyzed at different stress intensity factor range, ΔK. The experimental results showed that the crack growth decelerates in the MMC layer side and maximum crack retardation occurs on the boundary of the bi-material system. Near the boundary of the bi-material, the crack tip becomes curved, which reduces the crack growth rate in the vicinity of the boundary of the bi-material even at higher ΔK. The particle-matrix interfacial debonding, as well as particle fracture, is observed in the hybrid MMC layer during fatigue loading.